Utilization Review of Antibiotics in the Treatment of Urinary Tract Infection - Waleed Zafar, Haleema Arshad, Rashida Hassn, Umar Faqooq, Tehreem Fatima, Abaid Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the rationality of pharmacotherapy of UTI and to identify drug related problems (DRPs) in the treatment of UTI. Methodology:, a prospective study was perfomed in Ayub Teaching Hospital Abbottabad Pakistan for a period of three months (December 2019 to March 2020) on 62 patients suffering from UTI. Data of patient disease and treatment was collected from patient medical chart record file and then pharmacotherapy was evaluated for accessing rationality and identification of DRP using standard book like British national formulary and standard treatment guidelines. Statistical analysis of the data was performed by using SPSS. Results: Result of this study showed that prevalence of UTI was more in female (67.74%) than males (32.25%). Patients belonging to the age group of 20-40 years were more prone to UTI. The most frequent problems were presence of drug interactions, dosage problems cases, overprescribing cases, therapeutic duplication cases and lack of cost effectiveness cases. After analyzing the use of antibiotics it was found that most widely used antibiotics in the treatment of UTI was ceftriaxone, followed by levofloxacin and ciprofloxacin. Culture Sensitivity test for appropriate selection of antibiotics was not perfomed in 80% of cases. Wrong dose of antibiotics was prescribed in 27.4% cases; therapeutic duplication of antibiotics was found in 6% of patient prescription and over usage of antibiotics was observed in 18% of cases. Conclusion: Irrational use of drugs especially antibiotics in the treatment of UTI can adversely affect desired therapeutic outcome, lead to therapy failure and emergence of resistance of antibiotics which is a major concern. Drugs for the treatment of UTI should be used rationally according to the need and standard prescribing protocol to improve patient therapeutic outcome and to decrease the adverse consequences of drug therapy. . Keywords: Urinary tract infection, drug related problems and antibiotic use